Representativeness of Offensive Scenarios to Evaluate Perceptual-Cognitive Skills of Water Polo Players - Filipe Casanova; Ricardo Pereira; Sofia Canossa; Maickel Padilha; Rafael Bagatin; Israel Teoldo; Sixto González-Víllora; Ricardo J. Fernandes; Fernando Tavares (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
The aim of this study was to trial several attacking offensive sequences as representative for further use in research on the perceptual-cognitive skills of water polo players. Elite water polo coaches were presented with separate test film sequences encompassing 80 structured water polo offensive plays. Each clip was approximately 6 s-7 s long with an inter-clip interval of 5 s-10 s, where a red dot was displayed on-screen at the start of the clip to indicate the area of first appearance of the ball. The order of presentation of the video clips was counterbalanced and randomly determined. The criteria were scored on a 5-point Likert-type scale. From the 80 clips presented, only 56 showed high agreement (W = 1; p < 0.05) and internal consistence reliability between the expert observers (α = 0.980; p < 0.05). Furthermore, a very high reproducibility (Z = 0; p = 1) was obtained between viewing sessions. The results obtained determine that 56 offensive scenarios were representative of the water polo game and as such may be useful in evaluating the perceptual-cognitive skills of the players.